Pengembangan Alat Kempa Panas (Hot Press) Penekanan Dongkrak Hidrolik untuk Pembuatan Papan Komposit ukuran 25 cm x 25 cm - Junaidi Junaidi (Jurnal Teknik Mesin, 2020)
Human needs with wood continue to increase along with the increasing population, on the other hand Indonesia has a very large supply of wood. One way to overcome this is by substituting the use of wood from composite board products from wood or non-wood waste materials such as sawdust, coconut fiber, OPEFB fiber, bamboo fiber, bagasse and others. Composite board manufacturing technology is strongly influenced by the temperature, time and pressure contained in the hot press, either the system works manually or mechanically. The use of a hot press machine has so far been simple using an electric heating element from an iron element. For a n area of 40 cm x 40 cm board molding required 2 iron elements, the heat generated is not optimal (up to 1200 C), to heat the board to 1500 C the heating element often breaks / burns, this is certainly less efficient. Stripe heater type electric heating element is a flat plate heating element (Hot Plate) which can be used to heat a flat surface on pressing lignocellulosic material. The purpose of this research is to engineer and design and manufacture small scale heat press for 40 cm x 40 cm mold size, to test hot press and to test the physical and mechanical properties of composite boards. From the results of the manufacture of hot pressing tools obtained tool size 100 cm x 60 cm using iron profile u size 12 cm x 6 cm x 6 cm with a thickness of 0.4 cm. The pressure unit consists of a base plate measuring 40 cm x 40 cm x 1.5 cm, a pressure plate measuring 40 cm x 40 cm x 0.8 cm, a heating element measuring 40 cm x 40 cm x 0.5 cm using a power of 1.5 Kw each one. The suppressor component uses a hydraulic jack with a pressure of 50 tons. The heating element circuit is contained in the electrical panel box consisting of MCB, sign lights, thermocouple, amperemeter, and electrical wires. From the results of the heat test on the surface of the pressure plate obtained heat spread evenly on the entire surface of the plate and the pressure applied to the pressure plate is able to withstand the pressure from the hydraulic jack with a flat surface shape.